Complex transmission of partiti-, ambi- and ourmiaviruses in the forest pathogen Heterobasidion parviporum - Kashif, Muhammad; Poimala, Anna; Vainio, Eeva J; Sutela, Suvi; Piri, Tuula; Dálya, László Benedek; Hantula, Jarkko (Virus research, 2024)
Utilizing Heterobasidion partitivirus 13 strain an1 (HetPV13-an1) and 15 strain pa1 (HetPV15-pa1) in co-infection is considered a potential biocontrol approach against Heterobasidion root and butt rot. Both partitiviruses mediate debilitating effects in most Heterobasidion host isolates and are generally transmitted efficiently between host strains. In this investigation, we conducted transmission experiments in the laboratory (in vitro) using several H. parviporum isolates to test whether using dual partitivirus infections is a more efficient way of transmitting viruses to new hosts compared to using single partitivirus infections, and whether co-occurring single-stranded RNA (ssRNA) viruses are co-transmitted during the process. The results showed that H. parviporum donors carrying both partitiviruses, HetPV13-an1 and HetPV15-pa1, transmitted HetPV15-pa1 more efficiently to recipients than the same donors infected with only HetPV15-pa1. In contrast, the transmission of HetPV13-an1 did not differ significantly between donors infected with both or only one partitivirus. Altogether, the transmission rates of HetPV13-an1 and HetPV15-pa1 were high on artificial media. Moreover, the transmission of the ssRNA viruses Heterobasidion ourmia-like virus 1(HetOlV1-pa7) and 4 (HetOlV4-an1) as well as Heterobasidion ambi-like virus 3 (HetAlV3-pa4) across different recipients were found to be variable. This study demonstrated for the first time the transmission of ambi- and ourmiaviruses between H. parviporum isolates in dual cultures and showed that H. parviporum mycelia can be cured of these ssRNA viruses using heat treatment.
Keywords: Transmission; RNA virová; Dual culture; Ourmiavirus; Forests; Mycovirus; Coinfection; Fungal Viruses; Plant Diseases; lesy; Ambivirus; RNA-viry; Heterobasidion; mykoviry; RNA Viruses; nemoci rostlin; RNA, Viral; Partitivirus; Basidiomycota